Buerger Allen Therapy and Foot Sensitivity in Diabetes Mellitus Patients: Terapi Buerger Allen dan Sensitivitas Kaki Pasien Diabetes Melitus - Mukaromah, Isna Aulia; Lestari, Diana Tri; Kartikasari, Fitriana (Universitas Muhammadiyah Sidoarjo, 2026)
Background: Diabetes mellitus is a persistent global health condition frequently accompanied by peripheral neuropathy, which presents as reduced foot sensitivity and elevates the risk of foot-related complications. Specific background: Sensory impairment in the lower extremities remains a common clinical concern among diabetes mellitus patients receiving care at primary health facilities. Knowledge gap: Existing studies largely emphasize peripheral circulation parameters, while focused evidence describing foot sensitivity changes remains limited. Aims: This study aimed to describe foot sensitivity among diabetes mellitus patients undergoing Buerger Allen therapy in a community health setting. Results: A quasi-experimental pretest–posttest control group design was conducted with 82 participants. Monofilament testing revealed notable sensory changes in the intervention group, whereas the control group demonstrated relatively stable sensory findings. Novelty: This study places foot sensitivity as a primary clinical outcome rather than a secondary circulatory indicator. Implications: The findings support the incorporation of structured lower-extremity exercise within routine nursing care to address early sensory disturbances in diabetes mellitus. Highlights Buerger Allen therapy was accompanied by distinct foot sensory findings. Monofilament testing identified sensory patterns across intervention and control groups. Foot sensitivity served as a clinically meaningful outcome in diabetes care. Keywords Diabetes Mellitus, Buerger Allen Therapy, Foot Sensitivity, Diabetic Neuropathy, Nursing Care